INFORMATION AND COMMUNICATION TECHNOLOGY IN HIGHER EDUCATION AS AN OBJECT OF PSYCHOLOGY-PEDAGOGICAL RESEARCHES (THE SECOND HALF OF XX CENTURY – BEGINNING OF XXI CENTURY) - Voronkin, О.С. (Journal of Information Technologies in Education (ITE), 2015)
The article presents the historical and pedagogical analysis of psychological and educational research of information and communication technologies from 1950 to the present time. The personal contribution of scientists in the study of ICT is described. Materials of periodicals and PhD theses are analyzed. Identified the following areas of dissertation researchs: a) psychological and pedagogical basis of programmed instruction, study aids and automation of the educational process; b) the use of automated (information) systems and training classes to build interactive learning systems, didactic capabilities of your computer; c) the problem of information culture (competence) of students (teachers); d) psychological, didactic, philosophical, methodological aspects of the organization of learning using ICT; e) the development of information and educational environment and information and communication technology of training.nIn addition to educational, psychological and other aspects of the use of ICT, important role belongs to the technological aids to support lifelong learning. The possible versions for the implementation of the forms of training activities in ICT environment - lectures, seminars, consulting, laboratory classes and webinars are considered. The author concludes that the most effective forms of learning activity involves a level of mastery of the material in which the student will be able to teach others.